Mechanical properties of advanced nanosturctured composite fibres containing carbon nanotubes and graphene - Young, Karen (Trinity College (Dublin, Ireland). School of Physics, 2012)
A comprehensive study of the mechanical properties of coagulation spun poly(vinyl) alcohol-nanotube composite fibres has been performed. A method has been developed to control and measure the nanotube volume fraction, Vf, in these fibres. Both the fibre modulus, Y, and strength, σB, scale linearly with up to a maximum effective nanotube content of Vf~10%, after which these properties remain constant. It was found that dY/dVf=254 GPa and dσB/dVf=2.8 GPa in the linear region.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin.